2011
DOI: 10.1074/jbc.m110.194209
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Outer Membrane Lipid Composition of the Gram-negative, Lipopolysaccharide-lacking Myxobacterium Sorangium cellulosum So ce56

Abstract: The Gram-negative myxobacterium Sorangium cellulosum So ce56 bears the largest bacterial genome published so far, coding for nearly 10,000 genes. Careful analysis of this genome data revealed that part of the genes coding for the very well conserved biosynthesis of lipopolysaccharides (LPS) are missing in this microbe. Biochemical analysis gave no evidence for the presence of LPS in the membranes of So ce56. By analyzing the lipid composition of its outer membrane sphingolipids were identified as the major lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 52 publications
(45 reference statements)
0
28
0
Order By: Relevance
“…Sphingolipids have also been shown to be involved in development in fungi (36), as an example of lower eukaryotic organisms. In myxobacteria, they have been described to be major lipids in the outer membrane of Sorangium cellulosum So ce56 (37) and as part of the lipidome of M. xanthus (5,26). However, no specific function has yet been assigned to them.…”
Section: Discussionmentioning
confidence: 99%
“…Sphingolipids have also been shown to be involved in development in fungi (36), as an example of lower eukaryotic organisms. In myxobacteria, they have been described to be major lipids in the outer membrane of Sorangium cellulosum So ce56 (37) and as part of the lipidome of M. xanthus (5,26). However, no specific function has yet been assigned to them.…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge, the occurrence of bacterial PI-Cers has never been previously described. It seems that sphingolipids are a common component of myxobacterial membranes, as Cers were found in Cystobacter fuscus ( 44 ), Cer phosphoethanolamines in Myxococcus stipitatus ( 45 ), and Cer phosphoethanolamines, ␤ -D-glucosylsphingenines, and even phosphonosphingolipids in Sorangium cellulosum So ce56 ( 46 ), where they serve together with ornithine-containing lipids and glycerol ether lipids as substitutes for missing lipopolysaccharides in the outer membrane ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 shows Ϫ ( 45,46 ). Molecular composition was confi rmed by high-resolution MS (see Table 3 ).…”
Section: Lipid Profi Le Of M Xanthusmentioning
confidence: 99%
“…For most Gram-negative bacteria, LPS is crucial for the survival, however, the recent discovery of the LPS-lacking Sorangium cellulosum proves that bacteria may survive without LPS (Keck et al 2011). LPS was discovered by the German physician and bacteriologist Richard Pfeiffer in 1892, during his studies on the virulence of Vibrio cholerae. He demonstrated that LPS was responsible for the toxicity of the heat-killed V. cholerae cells (Beutler and Rietschel 2003;Lüderitz et al 1982;Wang and Quinn 2010).…”
Section: Lps: the Multifaceted Surface Componentmentioning
confidence: 99%